2002
DOI: 10.1182/blood.v99.9.3432
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-catalyzed cleavage and activation of Mst1 correlates with eosinophil but not neutrophil apoptosis

Abstract: We have examined the role of caspasemediated cleavage of the Ste20-like kinases, mammalian sterile 20-like 1 and 2 (Mst1/Mst2), in the mechanism of human eosinophil and neutrophil apoptosis. Initial measurements of kinase activity, using myelin basic protein (MBP) as a substrate in "in-gel" renaturation assays, showed that constitutive eosinophil and neutrophil apoptosis were associated temporally with the activation of a 36-kd MBP kinase (p36 MBPK) and a 34-kd MBP kinase (p34 MBPK), respectively. A constituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…[7][8][9] Furthermore, 36-kDa Mst1 is activated during apoptosis by anti-Fas antibody in human eosinophils and CD4 ϩ T-lymphocytes, but not in human neutrophils. 12,13) In the present study, activation of 36-kDa MBP kinase by antiFas antibody, dexamethasone and aminophylline also paralleled our observation of histone H2B phosphorylation. Cheung et al 10) demonstrated that catalytic 36-kDa Mst1 phosphorylated histone H2B in HL-60 cells.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…[7][8][9] Furthermore, 36-kDa Mst1 is activated during apoptosis by anti-Fas antibody in human eosinophils and CD4 ϩ T-lymphocytes, but not in human neutrophils. 12,13) In the present study, activation of 36-kDa MBP kinase by antiFas antibody, dexamethasone and aminophylline also paralleled our observation of histone H2B phosphorylation. Cheung et al 10) demonstrated that catalytic 36-kDa Mst1 phosphorylated histone H2B in HL-60 cells.…”
Section: Discussionsupporting
confidence: 75%
“…12,13) In the present study, we investigated the effect of dexamethasone and aminophylline (a theophylline dimer) on survival of T-lymphocytic leukemia Jurkat and promyelocytic leukemia HL-60 cells.…”
Section: -9)mentioning
confidence: 99%
See 1 more Smart Citation
“…6B, lane 3), the mass of cyclin D3 is comparable to that seen in lane 1. Inclusion of a caspase inhibitor, known to effectively increase eosinophil survival in the absence of added cytokine (100 M Z-Asp-CH 2 -[(2,6-dichlorobenzoyl)oxy]methane) (33), did not attenuate the decrease in cyclin D3 protein levels (Fig. 6B, lane 4), whereas an inhibitor of the ubiquitin proteosome system, MG115 (50 M), prevented the loss of immunoreactive cyclin D3 (Fig.…”
Section: Regulation Of Cyclin D3 Protein Expression In Eosinophils Bymentioning
confidence: 99%
“…MST1, for example, can induce apoptosis and nuclear condensation in BJAB, 293T, and COS-1 cells (15,46,47), and MST1 activity correlates with eosinophil apoptosis (10). Expression of MST3 in HEK293 cells leads to DNA fragmentation and apoptosis (19).…”
mentioning
confidence: 99%